Hz. Peygamber’in hadisleri ışığında çocuğun eğitiminde oyunun yeri - Turhan, Afife (My University, 2004)
Oyun, çocuğun eğitimi ve kişiliğinin gelişiminde ilk ve önemli adımdır. Bir çocuğun yaşamında en çok yer alan etkinlik oyundur. Çocuk için oyun, gıdaya olan ihtiyaç gibi temel bir ihtiyaçtır. Çocuk oynadıkça duyuları gelişir, becerileri artar. Çünkü oyun, çocuğun en doğal öğrenme ortamıdır, gelecek hayata hazırlıktır. Hz.Peygamber çocuğun hayatında bu denli önemli olan oyun konusuyla yakından ilgilenmiş, çocuklarla bizzat oynamıştır. Çocukların akranlarıyla oynamalarını teşvik etmiş, oyunlarına mani olmamış, gerektiğinde onlarla çocuk olmuştur. Bu konuda anne ve babalara, eğiticilere büyük sorumluluk düştüğünü de gerek sözleriyle gerekse uygulamalarıyla göstermiştir. Kısacası; oyun çocuğun gelişimi ve kişilik kazanmasında çok önemli bir unsurdur. Onun fiziksel, sosyal, duygusal, dilsel ve zihinsel gelişimine büyük katkı sağlar. Çocuklara oyun imkanı hazırlamada, onlarla çocuklaşmaları hususunda, yetişkinlere, anne ve babalara en güzel örnek Hz.Peygamber'in uygulamaları, sözleri, kısacası onun yaşayışıdır. Name and Surname: Afife Turhan Field: Theology Programme: Philosophy and Religious Sciences Supervisor: Professor M. Faruk Bayraktar Degree Awarded and Date: Master - June 2004 Game, Education, Child, Prophet

THE PLACE OF GAMES IN THE EDUCATION OF A CHILD, IN THE LIGHT OF THE HOLY PROPHET'S HADITH. Game is the first and important step in the education and character development of a child. It is an activity that plays a great role in a child's life. Game is a vital need for a child like the need for food. As the child plays his senses develop and skills improve. Since, game is the most natural learning environment of a child, preparing him for the future. The holy prophet (P.B.U.H.) has shown a great interest to the matter of play that has a high importance in a child's life and he himself has played with children. He has encouraged children to play with their peers, when necessary acted as a child with them and hasn't prevented their play. He has shown that a high responsibility is on the parents and teachers alike on this matter with his statements and practices. Shortly, game is a very important element in gaining the child's character and his development. It has a great contribution to his physical, social, emotional, linguistic and mental development. The best example for parents and grown ups on preparing game playing opportunities for children and on acting as a child with them is the Holy Prophet's (P.B.U.H.) practices, statements, briefly his way of life.
Keywords: Çocuk Gelişimi; Sosyal guruplar; Toplum bilimleri; Yaş gurupları